Reading and Writing Connections: A Way to Motivate Students to Read - Elizabeth Barragán Hernández; Sandra Torres Weissleder (Asociación Colombiana de Profesores de Ingles, 2016)
Throughout our teaching experience we have seen that in general, students are not motivated when reading is part of the tasks to develop in specialized subjects in the tertiary level. This is the case of students of VI semester at the Distrital University in Semantics and Pragmatics Analysis in which they are required to read about topics that deal with the subject mentioned above. The possible reasons why students did not want to read might be the lack of purpose to do it. Therefore, we decided to find a solution to this situation. After doing some literature review we agreed on implementing some of Vivian Zamel and Haines' ideas to overcome the problem. According to Zamel, one of the ways to establish a purpose when reading, is to connect writing in the process of reading and to develop an information and research project in which students develop reading comprehension and writing skills. This paper is intended to help other teachers motivate their students to read with a defined purpose.